Graphene modified antistatic film and preparation method thereof

By modifying graphene and combining with conductive composite resin, a crosslinkable self-repairing structure is formed, which solves the toughness and thermal stability of polylactic acid film materials, and achieves good anti-static properties to meet the multiple demands of the market for packaging materials.

CN119735841AActive Publication Date: 2025-04-01SHANGHAI JINGHOU ELECTRONIC TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510237987.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-03
Publication Date
2025-04-01
Estimated Expiration
2045-03-03

AI Technical Summary

Technical Problem

Polylactic acid film materials have problems of poor toughness and poor thermal stability. At the same time, after adding conductive fillers or conductive polymers to improve anti-static ability, these problems in the materials are further aggravated and cannot meet market demand.

Method used

By modifying the graphene and adding conductive composite resin, cross-linking and self-repairing structures can be formed with end maleimide polylactic acid resin, solving toughness and thermal stability problems, and also having good anti-static properties.

Benefits of technology

It has achieved the improvement of toughness and thermal stability of polylactic acid film materials, and has good anti-static properties to meet the multiple demands of the market for packaging materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of anti-static films, in particular to a graphene modified anti-static film and a preparation method thereof.The graphene modified anti-static film is prepared from, by weight, 45-50 parts of polylactic acid, 12-14 parts of maleimide-terminated polylactic acid, 6-8 parts of conductive composite resin, 3-5 parts of modified graphene and 2-4 parts of antioxidant; graphene is modified, conductive composite resin is added, a cross-linked self-repairing structure can be formed between the graphene and maleimide-terminated polylactic acid resin, the problems of poor toughness and poor thermal stability of a polylactic acid thin film material are solved, and meanwhile, due to the combined action of the conductive composite resin and the modified graphene, the thermal stability of the polylactic acid thin film material is improved. The anti-static performance is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of antistatic films, and in particular to a graphene-modified antistatic film and a preparation method thereof. Background Art

[0002] With the development of the market, people are paying more and more attention to the "white pollution" problem of plastic packaging materials. Polylactic acid film material is a degradable thermoplastic material with good biocompatibility, thermoplastic processability, good grease resistance and oil resistance. However, polylactic acid film material also has the problems of poor toughness and poor thermal stability. At the same time, due to some market demands, packaging materials are required to have good anti-static ability. At present, conductive fillers or conductive polymers are usually added to improve their anti-static ability. However, the addition of these materials will further highlight the problems of poor toughness and poor thermal stability of polylactic acid film materials, which can no longer meet market demand. Summary of the invention

[0003] The purpose of the present invention is to provide a graphene-modified antistatic film and a preparation method thereof. By modifying the graphene and adding a conductive composite resin, it can form a cross-linked self-healing structure with the terminal maleimide polylactic acid resin, thereby solving the problems of poor toughness and poor thermal stability of the polylactic acid film material. At the same time, due to the combined effect of the conductive composite resin and the modified graphene, it also has good antistatic properties.

[0004] The object of the present invention can be achieved by the following technical scheme: A method for preparing a graphene-modified antistatic film, prepared by the following steps: Step S1: weighing the following raw materials in parts by weight: 45-50 parts of polylactic acid, 12-14 parts of maleimide-terminated polylactic acid, 6-8 parts of conductive composite resin, 3-5 parts of modified graphene and 2-4 parts of antioxidant; Step S2: polylactic acid, maleimide-terminated polylactic acid, conductive composite resin, modified graphene and antioxidant are mixed and fed into a twin-screw extruder, melted and plasticized at a temperature of 160-170° C., a pressure of 2-2.2 MPa, and a rotation speed of 200-240 rpm, extruded and pressed into sheets, and then stretched, rolled and cut at a temperature of 140-160° C. and a stretching speed of 100 m / min to obtain a graphene-modified antistatic film; The polylactic acid is Hongfuyuan plasticized PLA 4032D; The maleimide-terminated polylactic acid is Starbeike Biotech PLA-Mal; The antioxidant is Aidico HP-10; The modified graphene is prepared by the following steps: Step A1: Mix expanded graphite, N,N-dimethylformamide and deionized water and ultrasonically disperse for 1-1.5h, then add titanium chloride solution and hydrochloric acid solution, react for 3-4h at a stirring rate of 400-500rpm and a temperature of 85-90°C, then add nitric acid solution and continue to react for 3-4h to obtain precursor 1, mix aluminum chloride, zinc chloride and ethanol, stir at a stirring rate of 160-180rpm and room temperature, stir and add acetylacetone, stir and react for 3-4h, then add precursor 1 and deionized water, ultrasonically disperse for 40-60min, react for 4-5h at a temperature of 85-90°C, centrifuge, filter, dry, transfer to a muffle furnace, and calcine at a temperature of 450°C for 2-2.5h to obtain precursor 2; The molar concentration of titanium chloride solution is 0.1 mol / L, the mass fraction of hydrochloric acid solution is 35%, the mass fraction of nitric acid solution is 10%, the dosage ratio of expanded graphite, titanium chloride solution, hydrochloric acid solution and nitric acid solution is 2-2.4 g: 38-40 mL: 180-200 mL: 15-18 mL; the dosage ratio of aluminum chloride, zinc chloride, ethanol, acetylacetone, precursor 1 and deionized water is 0.007-0.0075 g: 0.18-0.19 g: 25-30 mL: 0.0032-0.0035 mol: 3-3.2 g: 35-40 mL; The expanded graphite is 325 mesh expanded graphite. During the reaction, under the action of ultrasound, the expanded graphite is mechanically exfoliated to form a multilayer graphene structure. At the same time, due to the addition of hydrochloric acid solution and nitric acid solution, the exfoliated multilayer graphene structure attracts positively charged titanium ions through electrostatic action, so that titanium oxide is deposited on the surface of the multilayer graphene structure to obtain a precursor 1. Then, acetylacetone is used as a chelating agent to chelate with aluminum ions and zinc ions to form a chelate. Through the adsorption effect between the chelate and the precursor 1, the chelate is adsorbed on the precursor 1. After calcination, a special structure of zinc oxide-doped aluminum oxide powder is formed on the surface of the precursor 1 to obtain a precursor 2. Step A2: 4-maleimidobenzoic acid, γ-glycidyloxypropyltrimethoxysilane and toluene are mixed, and the mixture is reacted for 4-6 hours under nitrogen protection, at a stirring rate of 180-200 rpm and a temperature of 60°C to obtain modified silane. Precursor 2, modified silane, ethanol and deionized water are mixed and ultrasonically dispersed, and glacial acetic acid is added under stirring at a stirring rate of 180-200 rpm and a temperature of 80°C, and the mixture is stirred and reacted for 6-8 hours to obtain modified graphene; The dosage ratio of 4-maleimidobenzoic acid and γ-glycidyloxypropyltrimethoxysilane is 0.01-0.012 mol: 0.012 mol; the dosage ratio of precursor 2, modified silane, ethanol, deionized water and glacial acetic acid is 1.4-1.6 g: 0.3-0.36 g: 15-20 mL: 5-8 mL: 0.08-0.1 mL; During the reaction, the carboxyl group in 4-maleimidobenzoic acid reacts with the epoxy group in γ-glycidyloxypropyltrimethoxysilane to obtain modified silane, which is then hydrolyzed in ethanol and deionized water and combined with the precursor 2 to obtain modified graphene. The conductive composite resin is prepared by the following steps: Step B1: epichlorohydrin and tetrabutylammonium hydrogen sulfate are mixed, stirred at a rate of 240-280 rpm and room temperature, and furfuryl alcohol is added, reacted for 4-6 hours, and then sodium hydroxide solution is added, and the reaction is continued for 2-3 hours to obtain intermediate a, and intermediate a, furfurylamine and toluene are mixed, stirred at a rate of 180-220 rpm and a temperature of 110-115° C., and reacted for 3-4 hours to obtain intermediate b; The mass fraction of sodium hydroxide solution is 50%, the dosage ratio of epichlorohydrin, tetrabutylammonium hydrogen sulfate, furfuryl alcohol, and sodium hydroxide solution is 1.1-1.12 mol: 3.5-3.8 g: 1-1.04 mol: 140-150 mL; the dosage ratio of intermediate a and furfurylamine is 0.18-0.19 mol: 0.09-0.095 mol; During the reaction, under the action of tetrabutylammonium hydrogen sulfate, the epoxy group in epichlorohydrin reacts with the hydroxyl group in furfuryl alcohol to form an ether bond and generate a hydroxyl group, and then under the action of sodium hydroxide solution, the newly generated hydroxyl group reacts with chlorine to form an epoxy group to obtain intermediate a, and the epoxy group in intermediate a reacts with the amino group in furfurylamine to generate a hydroxyl group to obtain intermediate b;

[0005] Step B2: polyethylene glycol, intermediate b and N, N-dimethylformamide are mixed, and isophorone diisocyanate is added under stirring conditions of a stirring rate of 160-180 rpm and a temperature of 65-70° C., and the mixture is reacted for 3-4 hours, and then sodium 2,4-diaminobenzenesulfonate is added, and the mixture is heated to 80-85° C., and the reaction is continued for 4-5 hours, and the mixture is cooled to room temperature and deionized water is added, and the stirring is continued for 30-40 minutes to obtain a polyurethane prepolymer system; The dosage ratio of polyethylene glycol, intermediate b, isophorone diisocyanate, sodium 2,4-diaminobenzenesulfonate and deionized water is 18-20 g: 0.01 mol: 0.045-0.048 mol: 0.01 mol: 120-150 mL; The polyethylene glycol is MCE PEG2000; During the reaction, the hydroxyl groups in the polyethylene glycol and the intermediate b react with the isocyanate in the isophorone diisocyanate to form a carbamate structure, and then sodium 2,4-diaminobenzenesulfonate is added to continue the reaction to form a urea structure, and then deionized water is added to obtain a polyurethane prepolymer system; Step B3: Mix the pyrrole and polyurethane prepolymer system, stir at a stirring rate of 150-180 rpm and room temperature, add hydrochloric acid solution, adjust the pH value to 1.5, then cool to 0-5°C and add ferric chloride solution, continue to react for 2.5-3h, and obtain a conductive composite resin; The mass fraction of hydrochloric acid solution is 5%, the mass fraction of ferric chloride solution is 10%, and the dosage ratio of pyrrole, polyurethane prepolymer system and ferric chloride solution is 0.042-0.044 mol: 90-100 mL: 110-120 mL; During the reaction, pyrrole is polymerized in the polyurethane prepolymer system under the action of ferric chloride solution by an in-situ chemical oxidation polymerization method to form a polypyrrole chain segment, which is covalently and non-covalently bonded with the polyurethane prepolymer to obtain a conductive composite resin. Beneficial effects of the invention: The invention discloses a graphene-modified antistatic film and a preparation method thereof. By modifying graphene and adding a conductive composite resin, it can form a cross-linked self-repairing structure with the terminal maleimide polylactic acid resin, thereby solving the problems of poor toughness and poor thermal stability of the polylactic acid film material. At the same time, due to the combined effect of the conductive composite resin and the modified graphene, it also has good antistatic properties. During the melt blending process, due to the presence of a large number of branched furan groups in the conductive composite resin, it reacts with the modified graphene and the maleimide groups in the terminal maleimide polylactic acid to form a cross-linked self-repairing ‌DA structure. The toughness and thermal stability of the antistatic film are effectively improved. By modifying graphene, graphene is compounded with titanium oxide, and a special structure of zinc oxide-doped aluminum oxide powder is formed on the surface, so that the modified graphene has good electrical conductivity. It is combined with a conductive composite resin containing a polypyrrole segment, thereby improving the antistatic performance of the film. At the same time, due to the presence of its maleimide structure, it can be effectively combined with modified silane, thereby avoiding its agglomeration in the matrix resin. Due to the covalent connection between the modified graphene and the matrix resin, it can act as a stress node when the film is subjected to external force, and also improves the mechanical properties of the antistatic film to a certain extent. DETAILED DESCRIPTION

[0006] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0007] Example 1 A method for preparing a graphene-modified antistatic film is prepared by the following steps: Step S1: weighing the following raw materials in parts by weight: 45 parts of polylactic acid, 12 parts of maleimide-terminated polylactic acid, 6 parts of conductive composite resin, 5 parts of modified graphene and 2 parts of antioxidant; Step S2: polylactic acid, maleimide-terminated polylactic acid, conductive composite resin, modified graphene and antioxidant are mixed and fed into a twin-screw extruder, melted and plasticized at a temperature of 160° C., a pressure of 2 MPa and a rotation speed of 200 rpm, extruded and pressed into sheets, and then stretched, rolled and cut at a temperature of 140° C. and a stretching speed of 100 m / min to obtain a graphene-modified antistatic film; The polylactic acid is Hongfuyuan plasticized PLA 4032D; The maleimide-terminated polylactic acid is Starbeike Biotech PLA-Mal; The antioxidant is Aidico HP-10; The modified graphene is prepared by the following steps: Step A1: Mix expanded graphite, N,N-dimethylformamide and deionized water and ultrasonically disperse for 1 hour, then add titanium chloride solution and hydrochloric acid solution, react for 3 hours at a stirring rate of 400 rpm and a temperature of 85°C, then add nitric acid solution and continue to react for 3 hours to obtain precursor 1, mix aluminum chloride, zinc chloride and ethanol, stir and add acetylacetone at a stirring rate of 160 rpm and room temperature, stir and react for 3 hours, then add precursor 1 and deionized water, ultrasonically disperse for 40 minutes, react for 4 hours at a temperature of 85°C, centrifuge, filter, dry, transfer to a muffle furnace, and calcine at a temperature of 450°C for 2 hours to obtain precursor 2; The molar concentration of titanium chloride solution is 0.1 mol / L, the mass fraction of hydrochloric acid solution is 35%, the mass fraction of nitric acid solution is 10%, the dosage ratio of expanded graphite, titanium chloride solution, hydrochloric acid solution and nitric acid solution is 2g:38mL:180mL:15mL; the dosage ratio of aluminum chloride, zinc chloride, ethanol, acetylacetone, precursor 1 and deionized water is 0.007g:0.18g:25mL:0.0032mol:3g:35mL; The expanded graphite is 325 mesh expanded graphite. Step A2: 4-maleimidobenzoic acid, γ-glycidyloxypropyltrimethoxysilane and toluene were mixed, and the mixture was reacted for 4 h under nitrogen protection, at a stirring rate of 180 rpm and a temperature of 60°C to obtain modified silane. Precursor 2, modified silane, ethanol and deionized water were mixed and ultrasonically dispersed, and glacial acetic acid was added under stirring at a stirring rate of 180 rpm and a temperature of 80°C, and the mixture was reacted for 6 h to obtain modified graphene. The amount ratio of 4-maleimidobenzoic acid and γ-glycidyloxypropyltrimethoxysilane is 0.01 mol: 0.012 mol; the amount ratio of precursor 2, modified silane, ethanol, deionized water and glacial acetic acid is 1.4 g: 0.3 g: 15 mL: 5 mL: 0.08 mL; The conductive composite resin is prepared by the following steps: Step B1: epichlorohydrin and tetrabutylammonium hydrogen sulfate are mixed, stirred at a stirring rate of 240 rpm and a temperature of room temperature, and furfuryl alcohol is added, and the reaction is carried out for 6 hours, and then a sodium hydroxide solution is added, and the reaction is continued for 3 hours to obtain intermediate a. Intermediate a, furfurylamine and toluene are mixed, and the reaction is carried out for 3 hours at a stirring rate of 220 rpm and a temperature of 110°C to obtain intermediate b; The mass fraction of sodium hydroxide solution is 50%, the dosage ratio of epichlorohydrin, tetrabutylammonium hydrogen sulfate, furfuryl alcohol, and sodium hydroxide solution is 1.12 mol: 3.5 g: 1 mol: 150 mL; the dosage ratio of intermediate a and furfurylamine is 0.19 mol: 0.09 mol; Step B2: polyethylene glycol, intermediate b and N,N-dimethylformamide were mixed, and isophorone diisocyanate was added under stirring conditions of a stirring rate of 180 rpm and a temperature of 65°C, and the mixture was reacted for 3 hours. Then sodium 2,4-diaminobenzenesulfonate was added, and the mixture was heated to 85°C and the reaction was continued for 4 hours. The mixture was cooled to room temperature and deionized water was added, and the mixture was stirred for 40 minutes to obtain a polyurethane prepolymer system. The dosage ratio of polyethylene glycol, intermediate b, isophorone diisocyanate, sodium 2,4-diaminobenzenesulfonate and deionized water is 18g:0.01mol:0.048mol:0.01mol:120mL; The polyethylene glycol is MCE PEG2000; Step B3: Mix the pyrrole and polyurethane prepolymer system, stir at a stirring rate of 150 rpm and room temperature, add hydrochloric acid solution, adjust the pH value to 1.5, then cool to 0°C and add ferric chloride solution, continue to react for 3 hours, and obtain a conductive composite resin; The mass fraction of the hydrochloric acid solution is 5%, the mass fraction of the ferric chloride solution is 10%, and the dosage ratio of the pyrrole, polyurethane prepolymer system and the ferric chloride solution is 0.044 mol: 90 mL: 120 mL.

[0008] Example 2 A method for preparing a graphene-modified antistatic film is prepared by the following steps: Step S1: weigh the following raw materials in parts by weight: 45 parts of polylactic acid, 14 parts of maleimide-terminated polylactic acid, 8 parts of conductive composite resin, 3 parts of modified graphene and 2 parts of antioxidant; Step S2: polylactic acid, maleimide-terminated polylactic acid, conductive composite resin, modified graphene and antioxidant are mixed and fed into a twin-screw extruder, melted and plasticized at a temperature of 160° C., a pressure of 2.2 MPa and a rotation speed of 200 rpm, extruded and pressed into sheets, and then stretched, rolled and cut at a temperature of 160° C. and a stretching speed of 100 m / min to obtain a graphene-modified antistatic film; The polylactic acid is Hongfuyuan plasticized PLA 4032D; The maleimide-terminated polylactic acid is Starbeike Biotech PLA-Mal; The antioxidant is Aidico HP-10; The modified graphene is prepared by the following steps: Step A1: Mix expanded graphite, N,N-dimethylformamide and deionized water and ultrasonically disperse for 1.5 hours, then add titanium chloride solution and hydrochloric acid solution, react for 3 hours at a stirring rate of 400 rpm and a temperature of 90°C, then add nitric acid solution and continue to react for 3 hours to obtain precursor 1, mix aluminum chloride, zinc chloride and ethanol, stir at a stirring rate of 180 rpm and room temperature, stir and add acetylacetone, stir and react for 3-4 hours, then add precursor 1 and deionized water, ultrasonically disperse for 40 minutes, react for 4 hours at a temperature of 90°C, centrifuge, filter, dry, transfer to a muffle furnace, and calcine at a temperature of 450°C for 2.5 hours to obtain precursor 2; The molar concentration of titanium chloride solution is 0.1 mol / L, the mass fraction of hydrochloric acid solution is 35%, the mass fraction of nitric acid solution is 10%, the dosage ratio of expanded graphite, titanium chloride solution, hydrochloric acid solution and nitric acid solution is 2.4 g: 38 mL: 200 mL: 15 mL; the dosage ratio of aluminum chloride, zinc chloride, ethanol, acetylacetone, precursor 1 and deionized water is 0.0075 g: 0.18 g: 25 mL: 0.0035 mol: 3.2 g: 35 mL; The expanded graphite is 325 mesh expanded graphite. Step A2: 4-maleimidobenzoic acid, γ-glycidyloxypropyltrimethoxysilane and toluene were mixed, and the mixture was reacted for 6 h under nitrogen protection, at a stirring rate of 180 rpm and a temperature of 60°C to obtain modified silane. Precursor 2, modified silane, ethanol and deionized water were mixed and ultrasonically dispersed, and glacial acetic acid was added under stirring at a stirring rate of 200 rpm and a temperature of 80°C, and the mixture was reacted for 6 h to obtain modified graphene. The amount ratio of 4-maleimidobenzoic acid and γ-glycidyloxypropyltrimethoxysilane is 0.012 mol: 0.012 mol; the amount ratio of precursor 2, modified silane, ethanol, deionized water and glacial acetic acid is 1.4 g: 0.36 g: 15 mL: 5 mL: 0.1 mL; The conductive composite resin is prepared by the following steps: Step B1: epichlorohydrin and tetrabutylammonium hydrogen sulfate are mixed, stirred at a stirring rate of 240 rpm and a temperature of room temperature, and furfuryl alcohol is added, and the reaction is carried out for 4 hours, and then a sodium hydroxide solution is added, and the reaction is continued for 2 hours to obtain intermediate a, and intermediate a, furfurylamine and toluene are mixed, and the reaction is carried out for 3 hours at a stirring rate of 180 rpm and a temperature of 110°C to obtain intermediate b; The mass fraction of sodium hydroxide solution is 50%, the amount ratio of epichlorohydrin, tetrabutylammonium hydrogen sulfate, furfuryl alcohol, and sodium hydroxide solution is 1.1 mol: 3.5 g: 1 mol: 140 mL; the amount ratio of intermediate a and furfurylamine is 0.18 mol: 0.09 mol; Step B2: polyethylene glycol, intermediate b and N,N-dimethylformamide were mixed, and isophorone diisocyanate was added under stirring conditions of a stirring rate of 160 rpm and a temperature of 65°C, and the mixture was reacted for 3 hours. Then sodium 2,4-diaminobenzenesulfonate was added, and the mixture was heated to 80°C and the reaction was continued for 4 hours. The mixture was cooled to room temperature and deionized water was added, and the mixture was stirred for 30 minutes to obtain a polyurethane prepolymer system. The dosage ratio of polyethylene glycol, intermediate b, isophorone diisocyanate, sodium 2,4-diaminobenzenesulfonate and deionized water is 18 g: 0.01 mol: 0.045 mol: 0.01 mol: 120 mL; The polyethylene glycol is MCE PEG2000; Step B3: Mix the pyrrole and polyurethane prepolymer system, stir at a stirring rate of 150 rpm and room temperature, add hydrochloric acid solution, adjust the pH value to 1.5, then cool to 0°C and add ferric chloride solution, continue to react for 2.5 hours, and obtain a conductive composite resin; The mass fraction of the hydrochloric acid solution is 5%, the mass fraction of the ferric chloride solution is 10%, and the dosage ratio of the pyrrole, polyurethane prepolymer system and the ferric chloride solution is 0.042 mol: 90 mL: 110 mL.

[0009] Example 3 A method for preparing a graphene-modified antistatic film is prepared by the following steps: Step S1: weigh the following raw materials in parts by weight: 50 parts of polylactic acid, 14 parts of maleimide-terminated polylactic acid, 8 parts of conductive composite resin, 5 parts of modified graphene and 4 parts of antioxidant; Step S2: polylactic acid, maleimide-terminated polylactic acid, conductive composite resin, modified graphene and antioxidant are mixed and fed into a twin-screw extruder, melted and plasticized at a temperature of 170° C., a pressure of 2.2 MPa and a rotation speed of 240 rpm, extruded and pressed into sheets, and then stretched, rolled and cut at a temperature of 160° C. and a stretching speed of 100 m / min to obtain a graphene-modified antistatic film; The polylactic acid is Hongfuyuan plasticized PLA 4032D; The maleimide-terminated polylactic acid is Starbeike Biotech PLA-Mal; The antioxidant is Aidico HP-10; The modified graphene is prepared by the following steps: Step A1: Mix expanded graphite, N,N-dimethylformamide and deionized water and ultrasonically disperse for 1.5 hours, then add titanium chloride solution and hydrochloric acid solution, react for 4 hours at a stirring rate of 500 rpm and a temperature of 90°C, then add nitric acid solution and continue to react for 4 hours to obtain precursor 1, mix aluminum chloride, zinc chloride and ethanol, stir and add acetylacetone at a stirring rate of 180 rpm and room temperature, stir and react for 4 hours, then add precursor 1 and deionized water, ultrasonically disperse for 60 minutes, react for 5 hours at a temperature of 90°C, centrifuge, filter, dry, transfer to a muffle furnace, and calcine at a temperature of 450°C for 2.5 hours to obtain precursor 2; The molar concentration of titanium chloride solution is 0.1 mol / L, the mass fraction of hydrochloric acid solution is 35%, the mass fraction of nitric acid solution is 10%, the dosage ratio of expanded graphite, titanium chloride solution, hydrochloric acid solution and nitric acid solution is 2.4 g: 40 mL: 200 mL: 18 mL; the dosage ratio of aluminum chloride, zinc chloride, ethanol, acetylacetone, precursor 1 and deionized water is 0.0075 g: 0.19 g: 30 mL: 0.0035 mol: 3.2 g: 40 mL; The expanded graphite is 325 mesh expanded graphite. Step A2: 4-maleimidobenzoic acid, γ-glycidyloxypropyltrimethoxysilane and toluene were mixed, and the mixture was reacted for 6 h under nitrogen protection, at a stirring rate of 200 rpm and a temperature of 60°C to obtain modified silane. Precursor 2, modified silane, ethanol and deionized water were mixed and ultrasonically dispersed, and glacial acetic acid was added under stirring at a stirring rate of 200 rpm and a temperature of 80°C, and the mixture was reacted for 8 h to obtain modified graphene. The amount ratio of 4-maleimidobenzoic acid and γ-glycidyloxypropyltrimethoxysilane is 0.012 mol: 0.012 mol; the amount ratio of precursor 2, modified silane, ethanol, deionized water and glacial acetic acid is 1.6 g: 0.36 g: 20 mL: 8 mL: 0.1 mL; The conductive composite resin is prepared by the following steps: Step B1: epichlorohydrin and tetrabutylammonium hydrogen sulfate are mixed, stirred at a stirring rate of 280 rpm and a temperature of room temperature, and furfuryl alcohol is added, and the reaction is carried out for 6 hours, and then a sodium hydroxide solution is added, and the reaction is continued for 3 hours to obtain intermediate a, and intermediate a, furfurylamine and toluene are mixed, and the reaction is carried out for 4 hours at a stirring rate of 220 rpm and a temperature of 115°C to obtain intermediate b; The mass fraction of sodium hydroxide solution is 50%, the dosage ratio of epichlorohydrin, tetrabutylammonium hydrogen sulfate, furfuryl alcohol, and sodium hydroxide solution is 1.12 mol: 3.8 g: 1.04 mol: 150 mL; the dosage ratio of intermediate a and furfurylamine is 0.19 mol: 0.095 mol; Step B2: polyethylene glycol, intermediate b and N,N-dimethylformamide were mixed, and isophorone diisocyanate was added under stirring conditions of a stirring rate of 180 rpm and a temperature of 70°C, and the mixture was reacted for 4 hours. Then sodium 2,4-diaminobenzenesulfonate was added, and the mixture was heated to 85°C and the reaction was continued for 5 hours. The mixture was cooled to room temperature and deionized water was added, and the mixture was stirred for 40 minutes to obtain a polyurethane prepolymer system. The dosage ratio of polyethylene glycol, intermediate b, isophorone diisocyanate, sodium 2,4-diaminobenzenesulfonate and deionized water is 20g:0.01mol:0.048mol:0.01mol:150mL; The polyethylene glycol is MCE PEG2000; Step B3: Mix the pyrrole and polyurethane prepolymer system, stir at a stirring rate of 180 rpm and room temperature, add hydrochloric acid solution, adjust the pH value to 1.5, then cool to 5°C and add ferric chloride solution, continue to react for 3 hours, and obtain a conductive composite resin; The mass fraction of the hydrochloric acid solution is 5%, the mass fraction of the ferric chloride solution is 10%, and the dosage ratio of the pyrrole, polyurethane prepolymer system and the ferric chloride solution is 0.044 mol: 100 mL: 120 mL.

[0010] Comparative Example 1 Compared with Example 3, in the preparation process of the graphene-modified antistatic film in Example 3, the modified graphene is replaced with CROOD TG1000 graphene, and the other steps are the same.

[0011] Comparative Example 2 Compared with Example 3, this comparative example is performed by removing pyrrole in the preparation process of the conductive composite resin in Example 3, and the other steps are the same.

[0012] Take the graphene-modified antistatic film obtained in Example 1, Example 2, Example 3, Comparative Example 1 and Comparative Example 2, and use a tensile testing machine to test its tear strength. The sample size is 50 mm × 10 mm, and the tear rate is 150 mm / min. Use a support-type impact testing machine to test its impact strength to determine its mechanical properties. The sample size is 50 mm × 10 mm. Refer to IEC61340-2-3. Use a heavy hammer surface impedance tester to test its surface resistance to determine its antistatic performance. The sample is repeatedly bent 100 times and aged in a UV aging box for 3d, and then its conductivity is tested, and its performance retention rate is calculated to determine its long-term use of antistatic performance retention. The test results are shown in Table 1 below. Test results table: Test items Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Tear strength (kN / m) 156.9 156.5 157.8 149.9 155.3 <![CDATA[Impact strength (kJ / m 2 )]]> 17.42 17.31 17.89 16.34 17.52 <![CDATA[Surface resistance (×10 8 Ω / sq)]]> 0.882 0.879 0.875 1.024 0.987 Performance retention rate (%) 93.41 93.59 93.70 85.31 89.72 It can be seen from the test results in the table shown that when Example 1, Example 2 and Example 3 are compared with Comparative Example 1 and Comparative Example 2, in Comparative Example 1, during the preparation process of the graphene-modified antistatic film in Example 3, the modified graphene is replaced with KRD TG1000 graphene. Due to the lack of modification of the graphene, it is unable to form a cross-linked self-healing structure, and lacks the special structure formed by it and the zinc oxide-doped alumina powder, which leads to a significant decrease in its mechanical properties, antistatic properties and antistatic properties after long-term use. In Comparative Example 2, pyrrole is removed during the preparation process of the conductive composite resin in Example 3. Due to the lack of polypyrrole chain segments, the conductivity of the conductive composite resin itself decreases, which leads to a decrease in its antistatic properties and antistatic properties after long-term use.

[0013] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0014] The above contents are merely examples and explanations of the concept of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing a graphene-modified antistatic film, characterized in that: It is prepared by the following steps: Step S1: weigh the following raw materials in parts by weight: 45-50 parts of polylactic acid, 12-14 parts of maleimide-terminated polylactic acid, 6-8 parts of conductive composite resin, 3-5 parts of modified graphene and 2-4 parts of antioxidant; Step S2: polylactic acid, maleimide-terminated polylactic acid, conductive composite resin, modified graphene and antioxidant are mixed and fed into a twin-screw extruder, melted and plasticized at a temperature of 160-170°C, a pressure of 2-2.2MPa and a rotation speed of 200-240rpm, extruded into sheets, and then stretched, rolled and cut at a temperature of 140-160°C and a stretching speed of 100m / min to obtain a graphene-modified antistatic film.

2. The method for preparing a graphene-modified antistatic film according to claim 1, characterized in that: The modified graphene is prepared by the following steps: Step A1: Mix expanded graphite, N,N-dimethylformamide and deionized water and ultrasonically disperse for 1-1.5h, then add titanium chloride solution and hydrochloric acid solution, react for 3-4h at a stirring rate of 400-500rpm and a temperature of 85-90°C, then add nitric acid solution and continue to react for 3-4h to obtain precursor 1, mix aluminum chloride, zinc chloride and ethanol, stir at a stirring rate of 160-180rpm and room temperature, stir and add acetylacetone, stir and react for 3-4h, then add precursor 1 and deionized water, ultrasonically disperse for 40-60min, react for 4-5h at a temperature of 85-90°C, centrifuge, filter, dry, transfer to a muffle furnace, and calcine at a temperature of 450°C for 2-2.5h to obtain precursor 2; In step A1: the molar concentration of the titanium chloride solution is 0.1 mol / L, the mass fraction of the hydrochloric acid solution is 35%, the mass fraction of the nitric acid solution is 10%, the amount ratio of expanded graphite, titanium chloride solution, hydrochloric acid solution and nitric acid solution is 2-2.4 g: 38-40 mL: 180-200 mL: 15-18 mL; the amount ratio of aluminum chloride, zinc chloride, ethanol, acetylacetone, precursor 1 and deionized water is 0.007-0.0075 g: 0.18-0.19 g: 25-30 mL: 0.0032-0.0035 mol: 3-3.2 g: 35-40 mL; Step A2: 4-maleimidobenzoic acid, γ-glycidyloxypropyltrimethoxysilane and toluene are mixed, and the mixture is reacted for 4-6 hours under nitrogen protection, at a stirring rate of 180-200 rpm and a temperature of 60°C to obtain modified silane. Precursor 2, modified silane, ethanol and deionized water are mixed and ultrasonically dispersed, and glacial acetic acid is added under stirring at a stirring rate of 180-200 rpm and a temperature of 80°C, and the mixture is stirred and reacted for 6-8 hours to obtain modified graphene; In step A2: the usage ratio of 4-maleimidobenzoic acid and γ-glycidyloxypropyltrimethoxysilane is 0.01-0.012 mol: 0.012 mol; the usage ratio of precursor 2, modified silane, ethanol, deionized water and glacial acetic acid is 1.4-1.6 g: 0.3-0.36 g: 15-20 mL: 5-8 mL: 0.08-0.1 mL.

3. The method for preparing a graphene-modified antistatic film according to claim 1, characterized in that: The conductive composite resin is prepared by the following steps: Step B1: epichlorohydrin and tetrabutylammonium hydrogen sulfate are mixed, stirred at a rate of 240-280 rpm and room temperature, and furfuryl alcohol is added, reacted for 4-6 hours, and then sodium hydroxide solution is added, and the reaction is continued for 2-3 hours to obtain intermediate a, and intermediate a, furfurylamine and toluene are mixed, stirred at a rate of 180-220 rpm and a temperature of 110-115° C., and reacted for 3-4 hours to obtain intermediate b; In step B1: the mass fraction of sodium hydroxide solution is 50%, the amount ratio of epichlorohydrin, tetrabutylammonium hydrogen sulfate, furfuryl alcohol, and sodium hydroxide solution is 1.1-1.12 mol: 3.5-3.8 g: 1-1.04 mol: 140-150 mL; the amount ratio of intermediate a and furfurylamine is 0.18-0.19 mol: 0.09-0.095 mol; Step B2: polyethylene glycol, intermediate b and N, N-dimethylformamide are mixed, and isophorone diisocyanate is added under stirring conditions of a stirring rate of 160-180 rpm and a temperature of 65-70° C., and the mixture is reacted for 3-4 hours, and then sodium 2,4-diaminobenzenesulfonate is added, and the mixture is heated to 80-85° C., and the reaction is continued for 4-5 hours, and the mixture is cooled to room temperature and deionized water is added, and the stirring is continued for 30-40 minutes to obtain a polyurethane prepolymer system; In step B2: the ratio of polyethylene glycol, intermediate b, isophorone diisocyanate, sodium 2,4-diaminobenzenesulfonate and deionized water is 18-20 g: 0.01 mol: 0.045-0.048 mol: 0.01 mol: 120-150 mL; Step B3: Mix the pyrrole and polyurethane prepolymer system, stir at a stirring rate of 150-180 rpm and room temperature, add hydrochloric acid solution, adjust the pH value to 1.5, then cool to 0-5°C and add ferric chloride solution, continue to react for 2.5-3h, and obtain a conductive composite resin; In step B3: the mass fraction of the hydrochloric acid solution is 5%, the mass fraction of the ferric chloride solution is 10%, and the amount ratio of pyrrole, polyurethane prepolymer system and ferric chloride solution is 0.042-0.044 mol: 90-100 mL: 110-120 mL.

4. A graphene-modified antistatic film, characterized in that: Prepared according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Biaxially stretched polylactic acid / graphene composite membrane

    CN103319864A

  • Preparation method and application of aluminum modified carrier type chromium-based catalyst

    CN108912257A

  • Thermoreversible crosslinking composition modified polylactic acid 3D (Three Dimensional) printing filament and preparation method thereof

    CN109504048A

  • Photocurable self-healing polyurethane acrylic resin and preparation method thereof

    CN110183587A